A contribuição do pensamento social de João Calvino para a formação do cidadão - Garcia, Adelson Luiz (2015)
It deals of a work that finds to show the contribution of the social thought of John Calvin to the formation of the citizen. Thinking about this topic, we study that in the end of the Middle Age there was a great migration of the population to the cities. Before it a well-known picture was of the peasant and now it goes by to be the picture of the townsman. Naturally this transformation there would be to change the focus of the communal life and consequently the life in society. It increases the intensity of the social ties and thereafter more social problems. The society in transformation will need solid and balanced structure to develop and maintain itself through the laws and citizens that will regulate these laws. During the Middle Age, there was little assistance to the small existing society. With the Renaissance and the Religious Reform of the Sixteenth Century new contours of social and assistance thoughts go by to be applied in the society in this time. In this yeast of social transformation arises the picture of the reformer John Calvin, that, grounded in the Bible Scriptures of Ancient and New Testament, brought to the society of his age, over his thoughts and ideas, new directions to the citizen and his army of citizenship. John Calvin, in spite of not to be a sociologist, and to be a theologian person, brought social ideas of living together and citizenship through of his works and of the example-model too, that was left in the city of Geneva, where he could apply all of his concepts related to the society. Therefore, aspect such as: politic-administrative, educational and assistance were punctual and outstanding in help that John Calvin gave to the government of the city of Geneva. His performance was so special that many others inhabitants from other regions of Europe came to Geneva to learn his model and they will take to his lands. The processes that involve the study of citizen and the exercise of citizenship are always discussed, since the society lives in constant transformations. However, the citizen must prioritize principles that must be applied in any kind of transformation that the society may have. The citizen is involved intrinsically with the society. He is an integral part of its. Thus, he needs of high level formation that takes to be a contribute agent of the society, aiming to the common good of the same. The citizen must act in the society to participate so good of his government, practicing justice, how as governed, obeying the laws and serving to the Magistrates and Governments. John Calvin took his teachings to the citizens for that they were good examples of the citizenship to the society.